Timing of chaotic terrain formation in Argadnel Regio, Europa, and implications for geological history. (1st October 2016) - Parro, Laura M.; Ruiz, Javier; Pappalardo, Robert T.
Abstract: Chaos terrains are among the most prominent landforms of Europa, and are generally among the youngest features recorded on the surface. Chaos units were formed by to endogenic activity, maybe related to solid-state convection and thermal diapirism in the ice shell, perhaps aided by melting of salt-rich ice bodies below the surface. In this work, we analyze the different units of chaotic terrain in a portion of Argadnel Regio, a region located on the anti-Jovian hemisphere of Europa, and their possible timing in the general stratigraphic framework of this satellite. Two different chaos units can be differentiated, based on surface texture, morphology, and cross-cutting relationships with other units, and from interpretations based on pre-existing surface restoration through elimination of a low albedo band. The existence of two stratigraphically different chaos units implies that conditions for chaos formation occurred during more than a single discreet time on Europa, at least in Argadnel Regio, and perhaps in other places. The existence of older chaos units on Europa might be related to convective episodes possibly favored by local conditions in the icy shell, such as variations in grain size, abundance of non-water ice-components, or regional thickness of the brittle lithosphere or the entire ice shell. Highlights: We have investigated two stages of chaos formation in Argadnel Regio. Chaos units show different levels of surface disruption and formed in different times. Other geological processes occurred in the interval between chaos events. Our observations in Argadnel Regio support a complex geological history for Europa.